(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Purpose: The purpose of this paper is to critique the suitability of macro prudential policy as a proactive and effective toolkit for mitigating financial system risk in developing economies. Design/methodology/approach: The author first discusses the causes of the 2007/2008 global financial crisis in developed and developing economies. The narration is to demonstrate that the causes, duration and amplitude of the crisis differ across jurisdictions, and any regulatory model that will be effective in mitigating future crises must take into cognizance the institutional peculiarities of those countries. Â Findings: The paper provides evidence on the difficulties of implementing the macro-prudential policy toolkits in developing economies because of their institutional and structural characteristics such as inflationary pressure, undiversified economy, lagging supervision, among others. Research Limitations/implication: There is paucity of substantial local literature on macro-prudential policy in developing economies, especially Africa. While this study is meant to close this gap, literature reviewed however, relied extensively on studies on developed economies. Practical implication: The extrapolation of prudential tools from developed economies requires serious caution by developing economies because of dissimilarities in economic structure, financial system, governance structure and causes of systemic risk, which may not be mitigated by macro-prudential toolkits. Originality and Value: The study adds value to the global discourse on regulatory models for mitigating systemic crisis by introducing the perspective of developing economies to the macro-prudential debate.